Towards a common agricultural policy in Africa? - Blizkovsky, Petr; Grega, Libor; Verter, Nahanga (My University, 2018)
The paper analyses the structure and level of international cooperation among African states in the area of agriculture and rural development. It focuses on the African Union (AU) and its eight Regional Economic Communities. The international cooperation schemes between the World Bank, EU, FAO and African countries in agricultural policy are reviewed. The paper concludes that, despite numerous cross-border initiatives, governance of agricultural policies in the pan-African context remains fragmented. Policy-making and cooperation schemes need to be stepped up to address continent-wide challenges in the sector. There is an urgent need for the AU and the EU to intensify their cooperation in agricultural policies and development. The AU in collaboration with its regional bodies should establish a common agricultural policy for the continent. Such initiatives need to be Africa-driven and adapted to African needs. The EU should only provide technical know-how and institutional support if welcomed by African partners. Collective action towards rural areas via greater coordination of African agricultural policies and actions would help to develop the missing institutional framework needed for agricultural development in the continent. Fostering economic growth through agricultural development and reforms may also lead to a reduction of migration as witnessed by the EU in the sixties.
Keywords: agriculture; cooperation; EU; integration; policy; programme